2010
DOI: 10.1074/jbc.m109.037622
|View full text |Cite
|
Sign up to set email alerts
|

Niemann-Pick C1 Functions Independently of Niemann-Pick C2 in the Initial Stage of Retrograde Transport of Membrane-impermeable Lysosomal Cargo

Abstract: The rare neurodegenerative disease Niemann-Pick Type C (NPC) results from mutations in either NPC1 or NPC2, which are membrane-bound and soluble lysosomal proteins, respectively. Previous studies have shown that mutations in either protein result in biochemically indistinguishable phenotypes, most notably the hyper-accumulation of cholesterol and other cargo in lysosomes. We comparatively evaluated the kinetics of [ 3 H]dextran release from lysosomes of wild type, NPC1, NPC2, and NPC1/NPC2 pseudo-double mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 47 publications
2
47
0
1
Order By: Relevance
“…Few other studies have identifi ed biochemical differences between cells lacking NPC1 and cells lacking NPC2. Using dextran to follow membrane-impermeable lysosomal cargo, Goldman and Krise found that NPC1 was involved in the initial late endosome/lysosome fusion, whereas NPC2 was required for membrane fi ssion from the nascent hybrid endosome/lysosomes and the release of lysosomal cargo-containing vesicles ( 37 ). Other studies have implicated NPC2 in the regulation of cell differentiation in adipocytes and fi broblasts, a role that has not been described for NPC1 ( 38,39 ).…”
Section: Y119smentioning
confidence: 99%
“…Few other studies have identifi ed biochemical differences between cells lacking NPC1 and cells lacking NPC2. Using dextran to follow membrane-impermeable lysosomal cargo, Goldman and Krise found that NPC1 was involved in the initial late endosome/lysosome fusion, whereas NPC2 was required for membrane fi ssion from the nascent hybrid endosome/lysosomes and the release of lysosomal cargo-containing vesicles ( 37 ). Other studies have implicated NPC2 in the regulation of cell differentiation in adipocytes and fi broblasts, a role that has not been described for NPC1 ( 38,39 ).…”
Section: Y119smentioning
confidence: 99%
“…Thus, although cholesterol accumulates in LEs/Ls, there is a defi cit of cholesterol in the ER so that the sterol response element-binding protein (SREBP) pathway ( 33 ) is enhanced, and the synthesis and uptake of cholesterol are increased ( 9,34 ). The impaired traffi cking of cholesterol in NPC-defi cient cells profoundly affects multiple cellular functions such as regulation of lysosomal calcium homeostasis ( 35 ), oxidative stress ( 36,37 ), and vesicle traffi cking pathways mediated by Rab proteins ( 28,29 ), as well as fusion of LEs/Ls ( 38 ). NPC1 defi ciency is particularly detrimental for the functioning of LEs/Ls in the brain ( 39 ).…”
mentioning
confidence: 99%
“…Third, in addition to extracellular recycling, NPC1 has also been shown to be necessary for the efficient fusion of lysosomes with late endosomes. 18 Continuous fusion of lysosomes with late endosomes creates hybrid organelles in which the bulk of the lysosomal cargo is degraded. 18,19 NPC1 dysfunction caused accumulation of lysososmal cargo, 18 again consistent with the results presented here which show that more LNP colocalize with late endosomes/lysosomes in the presence of NP3.47.…”
Section: Discussionmentioning
confidence: 99%
“…18 Continuous fusion of lysosomes with late endosomes creates hybrid organelles in which the bulk of the lysosomal cargo is degraded. 18,19 NPC1 dysfunction caused accumulation of lysososmal cargo, 18 again consistent with the results presented here which show that more LNP colocalize with late endosomes/lysosomes in the presence of NP3.47. An additional question concerning the mechanism of NP3.47 is whether it applies to other forms of endocytosis.…”
Section: Discussionmentioning
confidence: 99%